(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this article, the performing arts were problematized in a scenario of extreme crisis, starting from the concept of art in an expended field. Possible aesthetic positions in this new context are discussed, based on critical considerations about the predominant modes of perception, strongly marked by virtual environments and neo-liberal subjectivity. It addressed the deepening of the dialogue between artists and researchers with traditional knowledge, in the construction of transversal knowledge and practices, thinking about artistic and aesthetic experience as micropolitics of perception.